Functional-semantic paradigms of voice сategory in the Kazakh language - Gaziza Imanaliyeva, Аnarkul Salkynbay, Nazyken Yegizbaieva, Shaigul Ramazanova, (Opción, 2019)
The purpose of the article is to define the formal and semanticsystem of voice category, their syntactic, communicative andsemanticpragmatic functions via comparative qualitative researchmethods. As a result, there is no difference between the paradigms ofthe form of the personal voice and impersonal voice categories in thestructure and meaning. In conclusion, the resulting (static) meaning ofan impersonal voice category form may indicate that the subject is notin the initial position and changes in the aspectual value.